Role of High Technology Medical Devices and Its Uses in Patient Care - Mrideema Yadav1 , Shailesh Kr. Singh2 , Amit Kumar Pandey3 , Aseervatham Achary4 , Sandeep Tiwari5 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The healthcare sector has a vision of providing the best medical facilities to their patients leading to betterhealth care and minimum of medical errors. The healthcare sector tries to provide the patients access to highquality medical devices, safe and security, effective technology and safe products for their health. Increasingcomplexity of medical technology and consequences for training and outcome of care. The healthcare sectorhas created a safe sense of services with enhanced and swift technology which is patient reported outcomesto help the patients rate the quality and working of the hospitals to get a clearer picture. This is possible onlywith the help of technology and this research paper is a primary data based exploration where techlogy is inthe centre.